ANALISIS PENGEMBANGAN STRATEGI UMKM BERBASIS DIGITAL UNTUK MEMBANGUN MENTAL TECHNOPRENEUR - Filda Angellia; Boy Firmansyah (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Information Technology is currently developing very quickly and rapidly to support the quality of work in all fields of activity. The implementation of technology is to simplify and minimize working time, including websites, social media, OA (Office Automation), and other technologies. Computerized technology includes software and hardware that performs the tasks desired by the user. Talking about current technology, it can be said that MSMEs (Micro, Small and Medium Enterprises) which are economic treasures that refer to productive economic activities are technology users. The use of technology that supports the performance and development of MSMEs is closely associated with the term technoprenueur. Technopreneurs are users of digital technology that is applied to the business they run. The existence of an innovative concept of information technology development in business processes in the form of a website will be able to help improve the business processes of business actors, because it is able to expand the marketing area and efforts to increase sales volume by building interactive communication relationships with consumers. Stages of developing a strategy for MSMEs with a digital basis to build a technopreneur mentality through stages including: applying the WebQual measurement method, then using the IPA (Importance Performance Analysis) support method, WebQual and IPA with the help of SPSS Software and website design according to the analysis results.